Medication error in general medicine department of tertiary care Koshi Zonal hospital in Nepal - Mustafa, Mohammad; Adhikari, Kajiram; Shah, Anil K.; Alam, Kadir; Jha, Rajesh; Sarraf, Deependra P. (International Journal of Basic & Clinical Pharmacology, 2024)
Background: Medication errors are the leading cause of patient harm, injuries and even death in hospitalized patients. It endangers patient safety and also increases the cost of treatment leading to enhanced financial burden to the individuals and the community as well. The study was aimed to determine the pattern of occurrence of medication errors. Methods: A cross-sectional study was conducted in 188 hospitalized patients in medical ward at a Zonal Hospital. Medication errors were identified and categorized by reviewing the cardex. The data were analyzed to determine the cause of medication errors including rates of harm to patients. The descriptive statistics frequency and percentage were calculated using Microsoft Excel 2007. The findings were presented as tables and graphs. Results: A total of 985 medication errors were found in 650 (38.3%) drugs prescribed in 177 (94.1%) patients. Approximately 72.9% of the errors reached the patients and 32.39% of the errors were harmful. The most common observed errors were administration errors (41.6%) followed by prescribing errors (36.5%), transcription errors (14.3%) and monitoring errors (7.5%). Omission of prescribing information (63.88%) and wrong dosing schedule (34%) were the most common type of prescribing and transcription errors respectively. Omission of dosages administration (57.32%) to patients was the most common types of administration error. All types of medication errors were highest in the alimentary tract and metabolism class of drugs (32.39%). Conclusions: Medication errors were associated with the majority of hospitalized patients signifying the requirement of immediate preventive strategies and policies to ensure patient safety.